Prevalence of nutrition and health-related claims on pre-packaged foods: a five-country study in Europe - Hieke, S; Kuljanic, N; Pravst, I; Miklavec, K; Kaur, A; Brown, K; Egan, B; Pfeifer, K; Gracia, A; Rayner, M (Multidisciplinary Digital Publishing Institute, 2016)
This study is part of the research undertaken in the EU funded project CLYMBOL ("Role of health-related CLaims and sYMBOLs in consumer behaviour"). The first phase of this project consisted of mapping the prevalence of symbolic and non-symbolic nutrition and health-related claims (NHC) on foods and non-alcoholic beverages in five European countries. Pre-packaged foods and drinks were sampled based on a standardized sampling protocol, using store lists or a store floor plan. Data collection took place across five countries, in three types of stores. A total of 2034 foods and drinks were sampled and packaging information was analyzed. At least one claim was identified for 26% (95% CI (24.0%-27.9%)) of all foods and drinks sampled. Six percent of these claims were symbolic. The majority of the claims were nutrition claims (64%), followed by health claims (29%) and health-related ingredient claims (6%). The most common health claims were nutrient and other function claims (47% of all claims), followed by disease risk reduction claims (5%). Eight percent of the health claims were children's development and health claims but these were only observed on less than 1% (0.4%-1.1%) of the foods. The category of foods for specific dietary use had the highest proportion of NHC (70% of foods carried a claim). The prevalence of symbolic and non-symbolic NHC varies across European countries and between different food categories. This study provides baseline data for policy makers and the food industry to monitor and evaluate the use of claims on food packaging.